Cytochemical flow analysis of intracellular G6PD and aggregate analysis of mosaic G6PD expression. (15th January 2018) - Kalnoky, Michael; Bancone, Germana; Kahn, Maria; Chu, Cindy S.; Chowwiwat, Nongnud; Wilaisrisak, Pornpimon; Pal, Sampa; LaRue, Nicole; Leader, Brandon; Nosten, Francois; Domingo, Gonzalo J.
Abstract: Background: Medicines that exert oxidative pressure on red blood cells (RBC) can cause severe hemolysis in patients with glucose‐6‐phosphate dehydrogenase (G6PD) deficiency. Due to X‐chromosome inactivation, females heterozygous for G6PD with 1 allele encoding a G6PD‐deficient protein and the other a normal protein produce 2 RBC populations each expressing exclusively 1 allele. The G6PD mosaic is not captured with routine G6PD tests. Methods: An open‐source software tool for G6PD cytofluorometric data interpretation is described. The tool interprets data in terms of % bright RBC, or cells with normal G6PD activity in specimens collected from 2 geographically and ethnically distinct populations, an African American cohort (USA) and a Karen and Burman ethnic cohort (Thailand) comprising 242 specimens including 89 heterozygous females. Results: The tool allowed comparison of data across 2 laboratories and both populations. Hemizygous normal or deficient males and homozygous normal or deficient females cluster at narrow % bright cells with mean values of 96%, or 6% (males) and 97%, or 2% (females), respectively. Heterozygous females show a distribution of 10‐85% bright cells and a mean of 50%. The distributions are associated with the severity of the G6PD mutation. Conclusions: Consistent cytofluorometric G6PD analysis facilitates interlaboratory comparison of cellular G6PD profiles and contributes to understanding primaquine‐associated hemolytic risk.